Viewpoint SCORE: Agile Research Group Management. - Hicks, Michael; Foster, Jeffrey S. (Communications of the ACM, 2010)
The article presents information on a computer-assisted method of managing an academic research group. Called SCORE (SCrum fOr REsearch), it is based on an agile software development technique called Scrum. It involves a two-part meeting structure, divided into regular status report meetings for the entire group, and on-demand research meetings which are devoted to mentoring doctoral degree students. The advantages of this approach are described in terms of time management, productivity, and knowledge sharing.